DNA sensing of dendritic cells in cancer immunotherapy - Qian, Wei; Ye, Jun; Xia, Sheng (Frontiers in Molecular Biosciences, 2024)
Dendritic cells (DCs) are involved in the initiation and maintenance of immune responses against malignant cells by recognizing conserved pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) through pattern recognition receptors (PRRs). According to recent studies, tumor cell-derived DNA molecules act as DAMPs and are recognized by DNA sensors in DCs. Once identified by sensors in DCs, these DNA molecules trigger multiple signaling cascades to promote various cytokines secretion, including type I IFN, and then to induce DCs mediated antitumor immunity. As one of the potential attractive strategies for cancer therapy, various agonists targeting DNA sensors are extensively explored including the combination with other cancer immunotherapies or the direct usage as major components of cancer vaccines. Moreover, this review highlights different mechanisms through which tumor-derived DNA initiates DCs activation and the mechanisms through which the tumor microenvironment regulates DNA sensing of DCs to promote tumor immune escape. The contributions of chemotherapy, radiotherapy, and checkpoint inhibitors in tumor therapy to the DNA sensing of DCs are also discussed. Finally, recent clinical progress in tumor therapy utilizing agonist-targeted DNA sensors is summarized. Indeed, understanding more about DNA sensing in DCs will help to understand more about tumor immunotherapy and improve the efficacy of DC-targeted treatment in cancer.